Q: What is the simplifyed answer to the expression 2x-2y 5z-2x-y 3z?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

The expression written in the question is the rational expression.

(3z + 5)(z -7)

3z-5

It is an algebraic expression that can be simplified to: 16z+11

-47 + 6z = 3z-2-3z -3z-47 + 3z = -2+47 +473z = 45/3 /3z = 15

Related questions

The expression written in the question is the rational expression.

help me .. .

(3z + 5)(z -7)

3z-5

It is an algebraic expression that can be simplified to: 16z+11

-47 + 6z = 3z-2-3z -3z-47 + 3z = -2+47 +473z = 45/3 /3z = 15

15 = 3z - 6 15 + 6 = 3z 3z = 21 z = 7

An algebra expression is 2 or more terms which does not contain an equality sign as for example 2x+y-3z

Collect all the letters on one side and the numbers on the other; what you do to one side of the equals you do to the other: 3z + 2 = 6z - 13 → 3z +2 - 3z = 6z - 13 - 3z → 2 = 3z - 13 → 2 + 13 = 3z - 13 + 13 → 15 = 3z → 3z = 15 (this is just changing the equals around so that the letter is on the left) → 3z ÷ 3 = 15 ÷ 5 → z = 5

33z - 4 - 20z - 5 simplified would be 13z - 1.

Since 9z is a multiple of 3z, it is automatically the LCM.

If you mean: 33z-4-20z-5 then it is 13z-9 when simplified